Enhancement And Optimization Of Dissolution Profiles Of Rivaroxaban Through Dispersed Systems - Selvaraja, Vinnashini; Wadhwani, Jagdish Srichand; Subramanian, Poonguzhali; Kalusalingam, Anandarajagopal; Khan, Abdullah; Siang, Tan Ching; Menon, Bama VV; Rajapandi, Senthilraj (Journal of Neonatal Surgery, 2025)
Background: The solubilization of poorly soluble drugs belonging to Class II of the Biopharmaceutical Classification System (BCS) is often a challenge in screening studies of new chemical substances as well as in formulation design and development. One of the most difficult aspects of formulation design is the Solubility properties. A number of methods can be used to improve the solubilization of poorly water-soluble drugs and further improve their bioavailability. Rivaroxaban, an anticoagulant, is classified as a poorly soluble BCS class II drug. Solid dispersion technologies provide promising results for improving the oral absorption and bioavailability of BCS class II drugs. The present study highlights the critical role of particle size reduction and increased surface area in improving the solubility, dissolution rate and subsequent bioavailability of rivaroxaban. Results: Incorporation of solid dispersions containing linear polymers further enhances these effects by creating larger, more porous particles that accelerate drug release. The strategic combination of HPMC and SLS in one formulation synergistically addresses the challenges associated with poorly soluble drugs. HPMC acts as a matrix former, facilitating the formation of a hydrogel layer around the drug particles and complementing the wetting agents of SLS that break down dissolution barriers. Consequently, the joint inclusion of HPMC and SLS not only exceeds the individual contributions of each component but also ensures improved therapeutic efficacy through improved drug release and absorption. The finer particle size formulation resulted in a higher dissolution rate of 100% after 30 minutes, likely due to the larger surface area of ​​the smaller particles, resulting in faster drug release and improved bioavailability. Furthermore, the amorphous state of rivaroxaban proves to be a key factor in enhancing drug release by eliminating the energy barrier associated with the dissolution of the crystal lattice. Conclusion: This innovative strategy holds promise for the advancement of pharmaceutical technology and enables the development of more effective drug formulations that overcome the limitations of poorly soluble drugs, thereby leading to better therapeutic outcomes for patients. The present study offers remarkable potential for revolutionizing drug delivery systems and ushers in the era of innovative medicines characterized by increased therapeutic efficacy, improved patient adherence and improved overall health outcomes